Atlas of hand anatomy and clinical implications - Yu, Han-Liang; Chase, Robert A; Strauch, Berish; Liang, Li-Guo (Mosby, 2004)
Here\'s a comprehensive new full-color atlas that demonstrates every aspect of hand anatomy, the cornerstone on which all successful hand surgery is built. It is written by respected plastic and orthopedic surgeons, who emphasize how readers can achieve excellent surgical results through a detailed understanding of the anatomic structures of the hand. Over 1,100 brilliant line drawings clarify etiology, structural mechanisms, pathologic clinical presentations, and much more.
Keywords: chirurgie; Hand; anatomie; ruka